Assessment for learning and cognitive process dimensions literacy of instructors in English - Semuel R. Olayvar; Christopher Dela Cruz Francisco (Institute of Advanced Engineering and Science, 2023)
The general problem of this study was to determine the literacy level of instructors in English on assessment for learning and cognitive process dimensions in terms of the following parameters such as classroom assessment objective, classroom assessment theoretical basis, types of tests, content, and performance standards and competencies, and cognitive process dimensions. To achieve this aim, the researchers involved five university administrators, 15 instructors in English, and 225 college students during the school year 2020-2021. The questionnaire on the literacy level of instructors in English on the assessment of learning and cognitive process dimensions was utilized. The results were processed using statistical packages for social sciences (SPSS) and presented using appropriate tables and texts. The findings revealed that: first, although instructors in English are utilizing specific, measurable, attainable, relevant, and time-bound (SMART) learning objectives, they still have to distinguish between three learning domains; secondly, while instructors in English are excellent in identifying the diversity of students, they have to look for various assessment tools; third, though they have flexibility in crafting learning goals, and assess students holistically, they need to be familiar with levels of cognitive process in achieving profound assessment for learning.